Operation characteristic of supercritical carbon dioxide-cooled reactor system under coordination control scheme. (26th June 2020) - Du, Xue; Hu, Junsheng; Xia, Genglei
Nuclear power plant is completely independent of air and has high power density, which improves unmanned marine vehicle maneuvering performance, maximum speed, and concealment. The supercritical carbon dioxide-cooled reactor system that has the advantages of compact system and high cycle efficiency is a promising energy conversion system candidate for generation IV reactors. However, due to the dramatic variations of supercritical fluid thermophysical properties, the operation of supercritical carbon dioxide-cooled reactor system is complex and it is difficult to control it. In this article, a mathematical model of supercritical carbon dioxide-cooled reactor system was established using the modified RELAP5 code, and two traditional coordination control schemes were used to study the system operation characteristics under load drop transient condition. Each key system parameter response characteristics was investigated. Finally, based on the research results, an optimized operation scheme that was proved to have better system control effect was proposed.